The Lambert-Topp-Leone distribution: an alternative for modeling proportion and lifetime data - Astorga, Juan M.; Iriarte, Yuri A. (Frontiers in Applied Mathematics and Statistics, 2025)
This article discusses the Lambert-Topp-Leone distribution as a flexible alternative for modeling proportion and lifetime data. By extending the Topp-Leone distribution, the proposed model offers greater flexibility in terms of skewness and kurtosis, making it suitable for a broader range of real-world applications. We examine key properties of the distribution, including its moments and behavior in terms of skewness and kurtosis. Parameter estimation using the maximum likelihood method is also discussed. A Monte Carlo simulation study is conducted to evaluate the performance of the estimators. Finally, to illustrate its practical utility, we apply the Lambert-Topp-Leone distribution to real-world datasets, demonstrating its superior fit for proportion and lifetime data compared to traditional models. The results suggest that this distribution provides a valuable tool for researchers and professionals in fields that require versatile modeling of bounded or positively skewed data.